Human C1q Induces Apoptosis in an Ovarian Cancer Cell Line via Tumor Necrosis Factor Pathway - Kaur, Anuvinder; Sultan, Sami H. A.; Murugaiah, Valarmathy; Pathan, Ansar A.; Alhamlan, Fatimah S.; Karteris, Emmanouil; Kishore, Uday (Frontiers in Immunology, 2016)
Complement protein C1q is the first recognition subcomponent of the complement classical pathway that plays a vital role in the clearance of immune complexes, pathogens, and apoptotic cells. C1q also has a homeostatic role involving immune and non-immune cells; these functions not necessarily involve complement activation. Recently, C1q has been shown to be expressed locally in the microenvironment of a range of human malignant tumors, where it can promote cancer cell adhesion, migration, and proliferation, without involving complement activation. C1q has been shown to be present in the ascitic fluid formed during ovarian cancers. In this study, we have examined the effects of human C1q and its globular domain on an ovarian cancer cell line, SKOV3. We show that C1q and the recombinant globular head modules induce apoptosis in SKOV3 cells in a time-dependent manner. C1q expression was not detectable in the SKOV3 cells. Exogenous treatment with C1q and globular head modules at the concentration of 10 µg/ml induced apoptosis in approximately 55% cells, as revealed by immunofluorescence microscopy and FACS. The qPCR and caspase analysis suggested that C1q and globular head modules activated tumor necrosis factor (TNF)-α and upregulated Fas. The genes of mammalian target of rapamycin (mTOR), RICTOR, and RAPTOR survival pathways, which are often overexpressed in majority of the cancers, were significantly downregulated within few hours of the treatment of SKOV3 cells with C1q and globular head modules. In conclusion, C1q, via its globular domain, induced apoptosis in an ovarian cancer cell line SKOV3 via TNF-α induced apoptosis pathway involving upregulation of Bax and Fas. This study highlights a potentially protective role of C1q in certain cancers.